(untitled) (Educational Dimension, 2024)
Technological and methodological aspects of using freeware software, such as GeoGebra, Wolfram|Alpha, Maxima, SageMath and GRAN1, for solving tasks with parameters, are presented in the article. Criteria were defined for selection of computer mathematics system (CMS) to solve tasks with parameters, including plotting a graph of a function given in explicit and implicit forms, using a parameter in a function’s analytical definition, and automatically changing the graph of a function depending on the parameter value; ability to changing the parameter step change; plotting of a tangent and a normal to a curve at a point; ability to change the scale; determination of the coordinates of the intersection of graphs of functions; obtaining an analytical solution. In the article, some examples were presented for graphic and analytical tasks that used CMS parameters. GRAN1 and GeoGebra are recommended to use for plotting and analyzing of the graphs.